Physiologic variations in blood plasminogen levels affect outcomes after acute cerebral thromboembolism in mice: a pathophysiologic role for microvascular thrombosis. (6th August 2016) - Singh, S.; Houng, A. K.; Wang, D.; Reed, G. L.
Abstract : Essentials Physiologic variations in blood plasminogen (Pg) levels may affect ischemic stroke outcomes. We tested Pg effects in a model with translational relevance to human thromboembolic stroke. A dose‐response exists between Pg levels and brain injury, fibrinolysis, barrier breakdown. Higher Pg levels reduce microvascular thrombosis and improve outcomes in ischemic stroke. Summary: Background and Objectives: Plasminogen appears to affect brain inflammation, cell movement, fibrinolysis, neuronal excitotoxicity, and cell death. However, brain tissue and circulating blood plasminogen may have different roles, and there is wide individual variation in blood plasminogen levels. The aim of this study was to determine the integrated effect of blood plasminogen levels on ischemic brain injury. Methods: We examined thromboembolic stroke in mice with varying, experimentally determined, blood plasminogen levels. Ischemic brain injury, blood–brain barrier breakdown, matrix metalloproteinase‐9 expression and microvascular thrombosis were determined. Results: Within the range of normal variation, plasminogen levels were strongly associated with ischemic brain injury; higher blood plasminogen levels had dose‐related, protective effects. Higher plasminogen levels were associated with increased dissolution of the middle cerebral artery thrombus. Higher plasminogen levels decreased blood–brain barrier breakdown, matrix metalloproteinase‐9 expression and microvascular thrombosis in the ischemic brain. In plasminogen‐deficient mice, selective restoration of blood plasminogen levels reversed the harmful effects of plasminogen deficiency on ischemic brain injury. Specific inhibition of thrombin also reversed the effect of plasminogen deficiency on ischemic injury by decreasing microvascular thrombosis, blood–brain barrier breakdown, and matrix metalloproteinase‐9 expression. Conclusions: Variation in blood plasminogen levels, within the range seen in normal individuals, had marked effects on experimental ischemic brain injury. Higher plasminogen levels protected against ischemic brain injury, and decreased blood–brain barrier breakdown, matrix metalloproteinase‐9 expression, and microvascular thrombosis. The protective effects of blood plasminogen appear to be mediated largely through a decrease in microvascular thrombosis in the ischemic territory.